Ethical inclusion: Risks and benefits of research from the perspective of perinatal people with opioid use disorders who have experienced incarceration. - Julia Reddy; Kristel Black; Keia Bazemore; Kiva Jordan; Jamie B Jackson; Andrea K Knittel (PLoS ONE, 2023)
Background Research ethics guidelines and emphasis on representation in research guide the inclusion of marginalized groups, including people with perinatal opioid use disorders (OUD) and people experiencing incarceration in the United States. However, insights from participants regarding the risks and benefits of participation are not adequately considered. The aim of this study was to examine the risks and benefits of research participation from the perspective of pregnant/postpartum people with OUD who have experienced incarceration. Design We recruited people who had experience with perinatal incarceration and were either currently pregnant or postpartum, and at least 18 years old. All participants met the clinical criteria for OUD. Our study did not have exclusion criteria based on gender, race, or ethnicity. Setting Participants were either currently incarcerated at the North Carolina Correctional Institute for Women in Raleigh, North Carolina, United States or had previously experienced perinatal incarceration and were recruited from a perinatal substance use disorder treatment program located in North Carolina. Participants Between 9/2021-4/2022, we completed 12 interviews with pregnant/postpartum people with OUD, approximately half who were currently incarcerated and half with a recent history of perinatal incarceration. Intervention/measurement Interviews were conducted via Webex phone or video. The interviews followed a scripted interview guide and lasted one hour on average. Interview transcripts were analyzed using the Rigorous and Accelerated Data Reduction technique to produce an overarching thematic framework. Findings Our analysis identified benefits, including the personal advantage of self-expression, helping others and contributing to change, and financial incentives. Risks included stigma and breach of confidentiality, misunderstanding of the distinction between research and advocacy, and limited ability to share their whole experience. Conclusions Participant-identified benefits of research mirrored those from other marginalized populations, though participant-identified risks were novel and nuanced. Recruitment and consent should move beyond normative research ethics committees protocol language to consider the perspectives of participants.